Symptomatic relief in medial opening wedge high tibial osteotomies for the treatment of knee osteoarthritis is influenced by concurrent procedures and preoperative pain level. Issue 1 (31st January 2018) - Figueroa, Francisco; Mhaskar, Vikram; Scholes, Corey; Pearlman, Alice; Coolican, Myles; Parker, David; Fritsch, Brett
Abstract : Objectives: Medial compartment osteoarthritis (OA) in the younger patient is technically challenging to treat. Medial opening wedge high tibial osteotomy (MOWHTO) is an option for surgical treatment; however, there remains a lack of evidence to establish the procedure as the preferred treatment option. The literature remains inconsistent with regard to patient characteristics and surgical factors that determine patient outcomes, particularly with respect to procedure survival and pain relief. The purpose of this study is to (i) describe the patient demographics and surgical outcomes of a consecutive series of MOWHTOs for treatment of medial knee OA; (ii) determine the procedure survivorship up to 10 years postsurgery and (iii) identify patient and surgery-related factors associated with pain relief following MOWHTO. Methods: A cohort of 210 patients was identified that underwent MOWHTO between 2002 and 2013. Patient demographics and complications were extracted from the clinical research database. Procedure survival analysis was conducted using a Kaplan-Meier analysis. All patients completed the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire preoperatively and postoperatively with pain relief identified as the difference between pre- and postoperative KOOS-pain subscale. A partial least square regression model was fitted to identify predictors of pain relief. Results: Males comprised 84% of the cohort, which had a median age of 51 years (95% CI 42 to 57 years). Patients were overweight on average, with a median BMI of 28.9 kg/m 2 (95% CI 23 to 36 kg/m 2 ) and 36% of patients underwent concomitant procedures. A complication rate of 3.8% was observed. Survivorship was 97.7% at 5 years and 80% at 10 years, with median time to conversion in those requiring total knee replacement of 7 years (95% CI 5 to 8). Patients undergoing cartilage treatment and bilateral procedures experienced increased pain relief compared with average, while there was reduced pain relief in patients with lower preoperative pain. Conclusion: MOWHTO is an effective procedure for relief of pain associated with medial knee OA, even in older and heavier patients. Patients and clinicians can expect an average procedure survival of 12.5 years and a maximum of 21 years, with effective pain relief influence by cartilage treatment and preoperative pain score. Level of evidence: IV. Case series.